Наукові основи очищення рослинних олій у конічних центрифугах - Дідур, Володимир Володимирович; Didur, Volodymyr; Журавель, Дмитро Павлович; Zhuravel, Dmytro; Повар, І. Ю.; Povar, I.; Колесніченко, І. А.; Kolesnichenko, I. (Запоріжжя: ТДАТУ, 2025)
UA: У статті подано результати аналізу сучасних підходів до механіко-технологічного очищення рослинних олій у конічних центрифугах. Розглянуто математичні моделі процесів очищення, наведено спро-щені формули та їх пояснення. Проаналізовано ефективність технологічних ліній очищення та перспективи використання фільтруючих матеріалів. /// EN: The article presents the results of an analysis of modern approaches to the mechanical and technological purification of vegetable oils in conical centrifuges. Mathematical models of the purification processes are considered, simplified formulas and their explanations are provided. The efficiency of technological purification lines is analyzed, and the prospects for the use of filtering materials are discussed. The production of vegetable oils requires highly efficient methods of purification from impurities. Traditional technological lines have high energy consumption and complex design, which reduces the economic performance of production. The use of conical centrifuges allows to ensure high-quality purification of oil through a combination of mechanical and filtration processes. Based on the analysis, an approach to building a generalized mathematical model of the efficiency of the oil purification technological line was substantiated. This approach became the basis for further research and allowed us to create a model that combines the physical laws of the process with economic indicators. The process of purifying vegetable oils is multi-stage and includes sedimentation of solid particles, filtration and centrifugal separation. Each of these stages is determined by both the physicochemical properties of the oil and the design parameters of the equipment. The use of conical centrifuges allows us to combine these processes in a single technological unit, which significantly increases the efficiency of purification. An analysis of the physical and mechanical and technological foundations of vegetable oil purification has been carried out, which proves the feasibility of using conical filter centrifuges. A simplified mathematical model of the purification process has been developed, which takes into account the properties of the oil, the characteristics of the filter material and the design parameters of the equipment. The use of natural zeolite filter material allows to increase the purification efficiency by 20–25% compared to conventional filtration systems. The proposed model makes it possible to predict the productivity of the technological line at the design stage, which contributes to the reduction of energy consumption and production costs. The results obtained can be used when designing new and modernizing existing technological lines for oil purification in the food industry.
Scientific bases of vegetable oil purification in conical centrifuges
Keywords: рослинні олії; очищення; центрифуга; математична модель; ефективність; vegetable oils; purification; centrifuge; mathematical model; efficiency